Quantification of Urban Groundwater Recharge: A Case Study of Rapidly Urbanizing Guwahati City, India - Jayashri Dutta; Runti Choudhury; Bibhash Nath (Urban Science)
The interaction between groundwater and urban environments is a growing concern for many rapidly urbanizing cities around the world, affecting both recharge and flow, since impervious surfaces reduce infiltration by increasing runoff, whereas over-abstraction leads to groundwater depletion and land subsidence. Additionally, industrial pollution and wastewater disposal contribute to contamination, impacting groundwater quality. The effective governance of groundwater within such urban locales necessitates a profound understanding of the hydrogeological context, coupled with robust tools for projecting fluctuations in groundwater levels and changes in water quality over time. We quantified urban groundwater recharge in Guwahati city, Assam, India, using the rainfall infiltration method and a numerical approach. Precipitation, evapotranspiration, runoff, and recharge from surface water bodies were considered the components of natural recharge, while leakages from water supply, domestic wastewater, and industrial wastewater were considered the components of urban recharge. The cumulative total of natural and urban components determines the actual groundwater recharge. The estimated natural groundwater recharge is 11.1 MCM/yr, whereas the urban groundwater recharge is 44.74 MCM/yr. Leakages from urban infrastructure resulted in significantly higher groundwater recharge than from natural inputs. Steady declines in groundwater recharge were observed from estimates taken at various time points over the past two decades, suggesting the need for prompt action to improve groundwater sustainability.